Exploring the process of health in mothers of children with cerebral palsy: Changing "clinical reasoning". (April 2022) - Dehghan, Leila; Dalvand, Hamid; Hadian Rasanani, Mohammad Reza; Kelly, Greg
Introduction: The issue of the health status of mothers of children with disability is one that is beginning to be addressed more fully. This study aimed to explore the process of health in mothers during caregiving of children with cerebral palsy (CP). Method: A qualitative research method with a grounded theory approach was used, including purposive and theoretical sampling. A constant comparative analysis method was adopted, and data were gathered from 15 mothers with CP children through interviews. Results: The results were grouped into six main categories: Self-neglecting of their health, facing challenges in caring their children, physical and psychosocial damages, perceiving threat of health problems from concern to action, trying to regain their health, and caring in a complex context. "Facing challenges in caring" was extracted as a core concept. Conclusion: Results showed an urgent need to establish family-centered services in clinical settings and change the "way of thinking" of the health provider system.